Analisis Etika Pendidik dalam Persepektif Al-Qur’an; Kajian Tafsir Al-Mishbah - Kurnia Sofiani, Ika; Hijratunnisak , Maya; Nabila, Mir’atun (Al-Mau'izhoh: Jurnal Pendidikan Agama Islam, 2023)
The phenomenon that occurs today, teachers in carrying out their duties do not pay much attention to the affective development that occurs to their students. Most of them today only abdicate their responsibility in conveying knowledge. Therefore, good ethics of a teacher are needed in teaching. Therefore, in this case, research will be carried out on educator ethics in the perspective of the Qur'an based on the study of the interpretation of Al-Mishbah by M. Quraish Shihab. The method used in this research is a literature review (library research) by collecting information based on reference sources in written form related to the research title. From this research, it can be concluded that based on the perspective of QS. Al-Imran verse 159 and QS. Al-A'raf verse 199 there are several ethics that must be possessed by educators. The ethics are: educators must be gentle, forgiving, willing to deliberate, able to invite good and leave all bad and trust Allah SWT.